Body Composition, Hand Grip Strength, and Leg Strength in Various Sports - Al Azim; Houda Bougrine; Jakir Hossain; Ismail Laher; Karuppasamy Govindasamy; Ayoub Saeidi; Hassane Zouhal (CV. FOUNDAE, 2025)
Background: Body composition, leg strength ratio, and handgrip strength could significantly affect and predict aspects of health and athletic performance. We explored the association between body composition (BC), leg strength (LSR), and hand grip strength (HGS) among university athletes in different sports.Aims: to investigate the multiple influences of these physical factors through other sports to provide a more integrated understanding of the total effect of these factors on athlete performance and selection.Methods: Sixty-six university athletes (age: 22.76± 2.11y, BMI 21.57± 3.04 kg/m2) were enrolled for our study. The participants (39 males and 27 females) participated in cricket, volleyball, and athletics. Body composition (BC), including lean body mass (LBM), muscle mass (MM), skeletal muscle mass (SMM), body fat mass (BFM), basal metabolic rate (BMR), hand grip strength (HGS), and leg strength ratio (LSR), was assessed. A chi-square test and independent sample t-tests analyzed the differences between categorical and continuous variables. A one-way ANOVA was used to analyze the multiple comparisons (BMR, LSR, BFM, and HGS) across cricket, volleyball, and track and field athletes.Results: The mean BFM in volleyball players was higher than in track and field athletes (14.20 ± 6.28 vs 8.44 ± 3.15, p<0.05). Analysis with a linear regression model adjusted for age, sex, BMI, and smoking habit indicated that LBM and BFM of participants were positively associated with HGS (p<0.05). However, an increase in HGS was associated with greater LSR in cricket (p< 0.001), volleyball (p <0.0001), and track and field athletes (p< 0.01).Conclusions: Our findings suggest that body composition, hand grip strength, and leg strength may be useful in player selection and improving performance for specific sports. Our results indicate increased hand grip strength is associated with greater leg strength.